Dual-Channel Supply Chain Coordination with Loss-Averse Consumers - Mengyu Zhang; Shanshan Ying; Xing Xu (Discrete Dynamics in Nature and Society)
Most studies on supply chain coordination assume that consumers are rational. However, with the development of e-commerce, consumer-bounded rationality has become an important issue with respect to supply chain coordination. Based on the assumption that some consumers are loyal to the offline shop and others are reference-dependent, this article examines the mechanism of vertical restraints and their competitive effects. This research study found that compared with the assumption of rational consumers used in previous literature, vertical restraints help internalize the “channel price gap externality” when consumers are loss averse. When separately operating, the offline shop will set a higher price due to its consumers’ higher loyalty and willingness to pay. However, given the positive externality of this price to the online retail sales, the offline price is still lower than the level under vertical integration. When the upstream manufacturer achieves supply chain coordination with vertical restraint contracts, the channel price gap externality is internalized, and the channel price gap expands to stimulate loss-averse consumers’ purchasing decisions.